2018
DOI: 10.1097/bto.0000000000000275
|View full text |Cite
|
Sign up to set email alerts
|

Blood Flow Restriction Therapy for Stimulating Skeletal Muscle Growth: Practical Considerations for Maximizing Recovery in Clinical Rehabilitation Settings

Abstract: Inactivity following injury and surgery due to pain, instability, or immobilization results in loss of muscle mass and function. As a result, both risk of reinjury and overall recovery time are a prime concern for clinicians and therapists trying to minimize these deleterious effects. While resistance exercise has been demonstrated to be highly effective in combating loss of muscle mass and function, it is often not advised for postoperative or injured patients because of elevated risk of injury or exacerbatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
38
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 93 publications
0
38
0
2
Order By: Relevance
“…Lately, the use of low-intensity (20-40% 1RM) resistance training in combination with blood flow restriction (BFR) has been advocated as a clinically relevant rehabilitation tool for patients not tolerating high muscle-tendon loads 17,18 . Of note, prospective studies have reported similar or improved clinical outcomes after BFR exercise compared to conventional rehabilitation following various types of knee injury [19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Lately, the use of low-intensity (20-40% 1RM) resistance training in combination with blood flow restriction (BFR) has been advocated as a clinically relevant rehabilitation tool for patients not tolerating high muscle-tendon loads 17,18 . Of note, prospective studies have reported similar or improved clinical outcomes after BFR exercise compared to conventional rehabilitation following various types of knee injury [19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…12,29,40,56 Although many of the mechanisms by which BFR may act on skeletal muscle remain under investigation, In-Depth previous reports indicate that performing low-intensity exercise under occluded conditions acutely stimulates muscle anabolism primarily via mitogen-activated protein kinase (MAPK) and mammalian target of rapamycin complex 1 (mTORC1) intramuscular signaling pathways; these pathways regulate skeletal muscle responses to metabolic and mechanical stress as well as signaling via the sensing of effectors released from contracting muscle or systemically that act in an autocrine, paracrine, or systemic fashion. 22,23,25,26,36 When performing low-intensity exercise with BFR, muscles are often exercised to fatigue in a manner that, due to the partial occlusion, temporarily prevents the removal of lactate, calcium, and other metabolites that may reduce intracellular and local blood pH and contribute to stress signaling. 36 This occurrence combined with increased muscle fiber recruitment due to fatigue, structural strain from muscle cell swelling, and release of signaling effectors from muscle (eg, myokines, local insulin-like growth factors [IGFs], microRNA) has been hypothesized to directly and indirectly stimulate muscle anabolism via the aforementioned signaling pathways in concurrence with other mechanisms involved in the regulation of cell growth and degradation.…”
mentioning
confidence: 99%
“…22,23,25,26,36 When performing low-intensity exercise with BFR, muscles are often exercised to fatigue in a manner that, due to the partial occlusion, temporarily prevents the removal of lactate, calcium, and other metabolites that may reduce intracellular and local blood pH and contribute to stress signaling. 36 This occurrence combined with increased muscle fiber recruitment due to fatigue, structural strain from muscle cell swelling, and release of signaling effectors from muscle (eg, myokines, local insulin-like growth factors [IGFs], microRNA) has been hypothesized to directly and indirectly stimulate muscle anabolism via the aforementioned signaling pathways in concurrence with other mechanisms involved in the regulation of cell growth and degradation. 1,20,25,39,55,60 Because metabolic and mechanical stress is primarily experienced by muscles distal to the site of occlusion, one may speculate that proximal muscles (where blood flow is not occluded) may not experience the same stimulatory effects with regard to changes in strength and muscle mass.…”
mentioning
confidence: 99%
See 2 more Smart Citations